An Analysis of the Stages of Community Empowerment in the Desa Cahaya Programby YBM PLN through the Assistance of the Tuna MSME Group "Selera Katong" in Oesapa Village, Kelapa Lima District, Kupang City - Gameta Syifa Ardina; Ety Rahayu (International Journal of Education, Vocational and Social Science, 2025)
The National Long-Term Development Plan (RPJPN) aims to achieve a poverty rate of 0% by 2045. However, the poverty rate in Indonesia has not demonstrated a significant decline, particularly in coastal areas such as East Nusa Tenggara (NTT). The poverty rate among traditional fishermen in NTT remains disproportionately high compared to the region's abundant marine resources. Various stakeholders have implemented empowerment programs, but their sustainability and effectiveness are limited, primarily due to inadequate mentoring. In response, the Baitul Maal PLN Foundation (YBM PLN) initiated the Desa Cahaya program to empower the Tuna MSME Group "Selera Katong" in Oesapa Village, Kelapa Lima District, Kupang Regency, East Nusa Tenggara. This study employs a qualitative research approach, utilizing a descriptive research design, with data collection conducted through interviews, observations, and documentation studies. The findings indicate that the assistance provided to the Tuna Fish MSME group "Selera Katong" is comprehensive, encompassing counseling and training activities related to the production process, as well as marketing support. The assistance aligns with the theoretical framework and stages of empowerment.